2013
DOI: 10.1002/cbic.201200764
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Biosynthesis of Fimsbactins A–F, Siderophores from Acinetobacter baumannii and Acinetobacter baylyi

Abstract: Novel chatechol/hydroxamate siderophores (named "fimsbactins") were identified in Acinetobacter baumannii ATCC 17978 and Acinetobacter baylyi ADP1. The major compound, fimsbactin A, was isolated from low-iron cultures of A. baylyi ADP1, and its chemical structure was elucidated by mass spectrometry, and detailed (1)H, (13)C and (15)N NMR spectroscopy. From inverse feeding experiments following HPLC-MS analysis, the structures of five additional derivatives were elucidated. The gene cluster encoding the fimsbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 26 publications
1
130
0
Order By: Relevance
“…More recently, it was reported that the A. baumannii ATCC 17978 strain, which could rely on the production and use of acinetobactin and fimsbactins to grow under free-iron limiting conditions (40), is also susceptible to Ga-PPIX. These observations further demonstrate that the antibacterial activity of Ga-PPIX is independent of the type or number of high-affinity iron chelators produced by a particular isolate.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was reported that the A. baumannii ATCC 17978 strain, which could rely on the production and use of acinetobactin and fimsbactins to grow under free-iron limiting conditions (40), is also susceptible to Ga-PPIX. These observations further demonstrate that the antibacterial activity of Ga-PPIX is independent of the type or number of high-affinity iron chelators produced by a particular isolate.…”
Section: Discussionmentioning
confidence: 99%
“…8). 203 Additional A. baumannii strains, as well as the nonpathogenic species A. baylyi , also contain the identical cluster. Six fimsbactin isoforms were identified that share a DHB moiety as well as an oxazoline ring derived from a serine residue.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…The compositions of bacteria related with iron cycling underwent great changes in different ARs and different stages. In the AR with UV/Cl 2 , at stage I, the relative abundance of nitrate-reducing bacteria (NRB) was 9.9%, and among them, 3.9% NRB were related to redox cycling of iron, such as Hyphomicrobium (3.7%) (Stein et al, 2001), and 6% NRB produced siderophores, including Sphingomonas (Duckworth et al, 2009), Brucella (Roop, 2012), Acinetobacter (Proschak et al, 2013) and Azospirillum (Loaces et al, 2011). The ironrespiring bacteria were 11.7%, predominantly including ironreducing bacteria (IRB) Acidobacterium (10.2%) (Nancucheo and Johnson, 2010) and iron-oxidizing bacteria (IOB) Pedomicrobium (1.3%) (Braun et al, 2009).…”
Section: 5mentioning
confidence: 99%